Fabrication of iron oxide nanoparticles from ammonia vapor and their importance in plant growth and dye degradation. (2nd January 2022) - Jain, Devendra; Kushwaha, Himmat Singh; Rathore, Kuldeep Singh; Stephen, Bjorn John; Daima, Hemant Kumar; Jain, Rohit; Singh, Abhijeet
Abstract: Iron oxide (Fe2 O3 ) nanoparticles are of great interest compared to their bulk counterpart due to their higher surface area, enhanced possibilities of bio-distribution and high rate of reactivity. In the present work, we report a simple, rapid, and cost-effective method for the synthesis of Fe2 O3 nanoparticles based on the aqueous-gaseous phase reaction of iron (III) chloride solution by ammonia vapor. Post-physicochemical characterization of these nanoparticles, we have further reported that these positive surface charged containing particles can increase the plant growth under in vitro conditions. Investigations on maize plant show that Fe2 O3 nanoparticles could have potential as a fertilizer substituent. Moreover, these particles were found to exhibit good photocatalytic activity against Rhodamine B, indicating their potential use toward soil remediation affected with industrial wastewater from dye industries.